Pengembangan Limbah Kulit Jagung Menjadi Produk Kerajinan Tangan Yang Bernilai Tambah - Alden Nelson; Antony Antony; Jolin Jolin; Lilis Lilis; Shelvina Shelvina; Melvin Sihombing (LPPM Universitas Internasional Batam, 2023)
Waste problem is a national issue that occurs in Indonesia. The dominant type of waste in Indonesia is organic or biodegradable waste, especially food waste. The city of Batam located in the Riau Archipelago Province is a popular tourist destination that generates large amounts of food waste. This problem is exacerbated by the fact that Batam is a strategic location for international shipping, resulting in a high volume of waste. Observations show that the most generated food waste in Batam City is corn husks, which are a by-product of staple crops in Indonesia, which presents a significant challenge in waste management. This article outlines the efforts made by the author to turn corn husk waste into unique handicraft products that can be sold on the market, namely the Rafflesia Dome and Wisata Nusantara Photo Frames, in order to increase the value of the waste and provide a sustainable solution to the food waste problem